CURRENT TRENDS OF DIGITAL-MARKETING IN THE CONDITIONS OF GLOBALIZATION - Karandyuk , Olga; Marchuk , Valeria (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2021)
The article states that the impact of Internet technologies on public life has become a prerequisite for creating a new type of marketing - digital marketing, a characteristic feature of which in addition to the specific environment of information dissemination was the need to develop an information product that meets consumer information needs. The authors note that under the current conditions of development of the world economy in general and the economy of Ukraine in particular, there are significant changes in the activities of enterprises and approaches to doing business. The development of globalization is analyzed and the emphasis is on its transformation into globalization processes. The most obvious change is that most companies and people have moved to the online environment. Current trends in the development of digital marketing in the context of globalization are considered. Important aspects of the impact of information technology on the change of everyday life and business activities are highlighted. The importance of digital marketing to meet the needs of a new generation of consumers has been identified. The main directions of using information technologies in marketing with their tendency to personification are determined. It is substantiated that the effective practice of digital marketing in the conditions of global informatization for enterprises is content marketing, which is based on the formation of interesting, relevant information material in accordance with the needs and desires of the consumer. Content should be relevant to current issues and issues of concern to consumers, have a clear and understandable structure of material, combine different tools of visualization and interactivity.Modern digital marketing is actively developing in the direction of video marketing, creation of audio content and voice processing systems; the role of messengers as a low-cost and more efficient SMM implementation environment is growing. Taking into account the analysis of modern scientific research, the authors noted that they have not substantiated the tools of Internet marketing, which are relevant in the context of globalization. Effective tools for promoting products on the Internet, which have developed significantly in recent years, are analyzed. The necessity of development of marketing Internet technologies of promotion of goods and services as a hybrid technology in the conditions of business globalization is substantiated. Taking into account the current trends in the development of online communications, the authors based on a study of modern publications summarized the current tools of digital marketing and systematized current trends in digital marketing. It is concluded that the further transformation of marketing in connection with the rapid development of technology.